Chronic Social Stress Inhibits Cell Proliferation in the Adult Medial Prefrontal Cortex: Hemispheric Asymmetry and Reversal by Fluoxetine Treatment - Czéh, Boldizsár; Müller-Keuker, Jeanine I H; Rygula, Rafal; Abumaria, Nashat; Hiemke, Christoph; Domenici, Enrico; Fuchs, Eberhard (Neuropsychopharmacology (New York, N.Y.), 2007)
Profound neuroplastic changes have been demonstrated in various limbic structures after chronic stress exposure and antidepressant treatment in animal models of mood disorders. Here, we examined in rats the effect of chronic social stress and concomitant antidepressant treatment on cell proliferation in the medial prefrontal cortex (mPFC). We also examined possible hemispheric differences. Animals were subjected to 5 weeks of daily social defeat by an aggressive conspecific and received concomitant, daily, oral fluoxetine (10 mg/kg) during the last 4 weeks. Bromodeoxyuridine (BrdU) labeling and quantitative stereological techniques were used to evaluate the treatment effects on proliferation and survival of newborn cells in limbic structures such as the mPFC and the hippocampal dentate gyrus, in comparison with nonlimbic structures such as the primary motor cortex and the subventricular zone. Phenotypic analysis showed that neurogenesis dominated the dentate gyrus, whereas in the mPFC most newborn cells were glia, with smaller numbers of endothelial cells. Chronic stress significantly suppressed cytogenesis in the mPFC and neurogenesis in the dentate gyrus, but had minor effect in nonlimbic structures. Fluoxetine treatment counteracted the inhibitory effect of stress. Hemispheric comparison revealed that the rate of cytogenesis was significantly higher in the left mPFC of control animals, whereas stress inverted this asymmetry, yielding a significantly higher incidence of newborn cells in the right mPFC. Fluoxetine treatment abolished hemispheric asymmetry in both control and stressed animals. These pronounced changes in gliogenesis after chronic stress exposure may relate to the abnormalities of glial cell numbers reported in the frontolimbic areas of depressed patients.